Rented, Crowded, and Unaffordable? Social Vulnerabilities and the Accumulation of Precarious Housing Conditions in Los Angeles. Issue 1 (2nd January 2017) - Díaz McConnell, Eileen
Abstract: Inspired by the social vulnerability paradigm employed in hazard and disaster research and recent work connecting personal and housing vulnerabilities, this study uses the first wave of Los Angeles Family and Neighborhood Survey data to: (a) examine immigrants' legal status as an independent social vulnerability that increases the risk of two or more of the following situations deemed to be precarious: renting, crowding, and unaffordable housing; (b) identify the individual-, household-, and neighborhood-level vulnerabilities associated with overlapping housing problems; and (c) identify the distribution of housing disadvantages across social groups. The sample comprises those born in the United States who are Black, White, and Latino, and three distinct Latino immigrant groups categorized by citizenship and legal status. The descriptive and multivariate regression results have implications for expanding hazard, disaster, and housing research and practice.